INCREASING BASIC LANGUAGE SKILLS OF YOUNG LEARNERS IN ENGLISH LESSONS. - Xolmurodova, Olima (Журнал иностранных языков и лингвистики, 2021)
Children are learning English at younger ages. In many countries, English is a compulsory subject in the early primary grades. In this article the authors researched and reviewed works by international academics on the research problem; established factors ensuring good learning and mastering of foreign language skills by young learners; and reasoned the importance of beginning teaching with speaking and listening, accompanied by writing and reading skills, in accordance with their age peculiarities.